Long Noncoding RNA Cardiac Physiological Hypertrophy–Associated Regulator Induces Cardiac Physiological Hypertrophy and Promotes Functional Recovery After Myocardial Ischemia-Reperfusion Injury. Issue 4 (27th July 2021) - Gao, Rongrong; Wang, Lijun; Bei, Yihua; Wu, Xiaodong; Wang, Jiaqi; Zhou, Qiulian; Tao, Lichan; Das, Saumya; Li, Xinli; Xiao, Junjie
Abstract : Background: The benefits of exercise training in the cardiovascular system have been well accepted; however, the underlying mechanism remains to be explored. Here, we report the initial functional characterization of an exercise-induced cardiac physiological hypertrophy–associated novel long noncoding RNA (lncRNA). Methods: Using lncRNA microarray profiling, we identified lncRNAs in contributing the modulation of exercise-induced cardiac growth that we termed cardiac physiological hypertrophy–associated regulator (CPhar). Mice with adeno-associated virus serotype 9 driving CPhar overexpression and knockdown were used in in vivo experiments. Swim training was used to induce physiological cardiac hypertrophy in mice, and ischemia reperfusion injury surgery was conducted to investigate the protective effects of CPhar in mice. To investigate the mechanisms of CPhar's function, we performed various analyses including quantitative reverse transcription polymerase chain reaction, Western blot, histology, cardiac function (by echocardiography), functional rescue experiments, mass spectrometry, in vitro RNA transcription, RNA pulldown, RNA immunoprecipitation, chromatin immunoprecipitation assay, luciferase reporter assay, and coimmunoprecipitation assays. Results: We screened the lncRNAs in contributing the modulation of exercise-induced cardiac growth through lncRNA microarray profiling and found that CPhar was increased with exercise and was necessary for exercise-induced physiological cardiac growth. The gain and loss of function of CPhar regulated the expression of proliferation markers, hypertrophy, and apoptosis in cultured neonatal mouse cardiomyocytes. Overexpression of CPhar prevented myocardial ischemia reperfusion injury and cardiac dysfunction in vivo. We identified DDX17 (DEAD-Box Helicase 17) as a binding partner of CPhar in regulating CPhar downstream factor ATF7 (activating transcription factor 7) by sequestering C/EBPβ (CCAAT/enhancer binding protein beta). Conclusions: Our study of this lncRNA CPhar provides new insights into the regulation of exercise-induced cardiac physiological growth, demonstrating the cardioprotective role of CPhar in the heart, and expanding our mechanistic understanding of lncRNA function, as well. Abstract : Supplemental Digital Content is available in the text.